Incidence rate and risk factors of pulmonary conditions three years post COVID-19 in Bronx, New York: a retrospective cohort study - Sonya S. Henry; Stephen H. Wang; Wei Hou; Tim Q. Duong (Scientific Reports)
Abstract This retrospective cohort study used propensity-matched cohorts with a 3-year follow-up (March 2020–July 2023) to determine incidence rates, relative risks, and risk factors for incident pulmonary conditions after COVID-19 exposure. Data were drawn from a multi-center health system in New York City. Participants had at least 30 days of follow-up and included patients with or without COVID-19 confirmed by PCR, diagnosed with lower respiratory tract infection (LRTI), or without COVID-19/LRTI testing. COVID-19 status was defined by positive PCR, LRTI requiring hospitalization, or neither. The final cohort (n = 69,632) comprised 1:1 propensity-matched comparisons based on age, sex, race/ethnicity, obesity, type II diabetes, hypertension, and smoking, stratified by hospitalization. Primary outcomes were incidence rates, hazard ratios (HRs), and incidence rate ratios (IRRs) for new-onset pulmonary conditions. The study included 34,816 matched COVID-19 survivors and 34,816 non-COVID survivors. Non-hospitalized COVID-19 patients had a threefold higher risk of incident pulmonary conditions compared to non-COVID controls (aHR = 3.36, 95% CI: 3.02–3.73). Hospitalized COVID-19 patients showed similar risk to hospitalized LRTI controls (aHR = 1.24, 95% CI: 0.84–1.84). Multiple sensitivity analyses were conducted. COVID-19 increases pulmonary risk in non-hospitalized patients but not in hospitalized cohorts compared with LRTI. These findings underscore the need for monitoring and intervention in at-risk individuals.